2007
DOI: 10.1158/1078-0432.ccr-07-0050
|View full text |Cite
|
Sign up to set email alerts
|

Intradermal CpG-B Activates Both Plasmacytoid and Myeloid Dendritic Cells in the Sentinel Lymph Node of Melanoma Patients

Abstract: Purpose: A decrease in the frequency and activation state of dendritic cells in the sentinel lymph node (SLN) has been observed in early stages of melanoma development. This may hinder the generation of effective antitumorT-cell responses and increase the likelihood of metastatic spread. Immunopotentiation of the melanoma SLN may therefore be a valuable adjuvant treatment option. One way to achieve this is through the use of bacterially derived unmethylated cytosinephosphate-guanine (CpG) DNA sequences that bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
98
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 47 publications
8
98
0
Order By: Relevance
“…In this setting, PF-3512676 was shown to induce the release of inflammatory cytokines and decrease the number of regulatory T cells observed in sentinel lymph nodes of patients with stage I to III melanoma (Molenkamp et al, 2007). Furthermore, both myeloid and pDCs were activated (Molenkamp et al, 2007), indicating that PF-3512676 clearly has immunomodulatory activity. In a different phase II study in patients (N ¼ 20) with metastatic melanoma treated with s.c. PF-3512676, two (10%) patients had a PR and three (15%) patients had stable disease (SD) (Pashenkov et al, 2006).…”
Section: Skin Cancersmentioning
confidence: 87%
See 2 more Smart Citations
“…In this setting, PF-3512676 was shown to induce the release of inflammatory cytokines and decrease the number of regulatory T cells observed in sentinel lymph nodes of patients with stage I to III melanoma (Molenkamp et al, 2007). Furthermore, both myeloid and pDCs were activated (Molenkamp et al, 2007), indicating that PF-3512676 clearly has immunomodulatory activity. In a different phase II study in patients (N ¼ 20) with metastatic melanoma treated with s.c. PF-3512676, two (10%) patients had a PR and three (15%) patients had stable disease (SD) (Pashenkov et al, 2006).…”
Section: Skin Cancersmentioning
confidence: 87%
“…Treatment was associated with increased levels of serum interleukin (IL)-6, IL12p40 and IP-10 in some patients, and cellular infiltrates of CD8 þ lymphocytes were found after treatment in most lesions. In a different trial involving patients with clinical stage I/II melanoma, surgical resection of the primary tumor was followed by randomization to receive either saline or PF-3512676 (8 mg) intradermally at the excision site, followed 1 week later by a sentinel lymph node procedure (Molenkamp et al, 2007). In this setting, PF-3512676 was shown to induce the release of inflammatory cytokines and decrease the number of regulatory T cells observed in sentinel lymph nodes of patients with stage I to III melanoma (Molenkamp et al, 2007).…”
Section: Skin Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Most likely, pDCs are not properly activated on uptake of tumor-derived substances because of the lack of danger signals (12). Recent studies have shown that in vivo TLR triggering with TLR-Ls, such as CpG, induced pDC activation, resulting in antitumor immunity and partial tumor regression (42)(43)(44). Furthermore, activated human pDCs pulsed with a tumor Ag primed IFN-g secreting Ag-specific CTLs (45).…”
Section: Discussionmentioning
confidence: 99%
“…27,41 Next to creating a beneficial milieu for inducing tumor-directed immunity, specific or enhanced targeting of TAAs to DCs has shown beneficial effects, for example by conjugating TAA to TLR ligands, 42 or generating antibody-antigen complexes. 43 These strategies may also be applied to apoptotic bleb-based vaccines.…”
Section: 1332mentioning
confidence: 99%